Immunological evaluation of peptide vaccination for cancer patients with the HLA ‐A11+ or ‐A33+ allele. Issue 4 (21st April 2017) - Sakamoto, Shinjiro; Matsueda, Satoko; Takamori, Shinzo; Toh, Uhi; Noguchi, Masanori; Yutani, Shigeru; Yamada, Akira; Shichijo, Shigeki; Yamada, Teppei; Suekane, Shigetaka; Kawano, Kouichiro; Naitou, Masayasu; et al.
Abstract : The HLA‐A11 or ‐A33 allele is found in approximately 18% or 10% of the Asian population, respectively, but each of which is a minor allele worldwide, and therefore no clinical trials were previously conducted. To develop a therapeutic peptide vaccine for each of them, we investigated immunological responses of advanced cancer patients with the HLA‐A11 + /A11 + ( n = 18) or ‐A33 + /A33 + ( n = 13) allele to personalized peptide vaccine (PPV) regimens. The primary sites of HLA‐A11+/A11+ or ‐A33+/A33+ patients were the colon ( n = 4 or 2), stomach (2 or 3), breast (3 or 2), lung and pancreas (2 or 2), and so on. For PPV, a maximum of four peptides were selected from nine different peptides capable of binding to HLA‐A11 and ‐A33 molecules based on the pre‐existing peptide‐specific IgG responses. There were no severe adverse events related to PPV. At the end of the first cycle, peptide‐specific CTL responses were augmented in 4/12 or 2/9 of HLA‐A11 + /A11 + or ‐A33 + /A33 + patients, while peptide‐specific IgG responses were augmented in 6/14 or 4/10 patients, respectively. Clinical responses consisted of four stable diseases and 14 progressive diseases in HLA‐A11 + /A11 + patients, versus seven and six in ‐A33 + /A33 + patients, respectively. Further clinical study of PPV could be recommended because of the safety and positive immunological responses. Abstract : IgG boosting were observed in HLA‐A11+/A11+ patients and HLA‐A33+/A33+ patients after personalized peptide vaccine(PPV). The patients with higher rate of changes of peptide‐specific IgG titers after 2nd cycle of vaccination showed longer prognosis than those with lower rate.